2020
DOI: 10.1016/j.arrct.2019.100035
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a 2-Week Pre-clerkship Residency Exploration Program on Specialty Interest and Understanding of Physical Medicine and Rehabilitation

Abstract: Objective To assess the effect the Pre-clerkship Residency Exploration Program (PREP) had on student career interest and improving understanding of physical medicine and rehabilitation (PMR). Design During a 2-week program, students were exposed to a PMR elective, workshop, career presentation, and panel discussion with PMR residents. Interest and understanding were assessed using pre- and postprogram questionnaires. Setting PREP was held at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Most (n = 12) focused on promoting and understanding intellectual well-being in medical education (Table 2). Five qualitative studies reported favourable outcomes; 3 studies concluded that formal audit is needed 34,79,77 and 2 studies uncovered shortcomings related to postgraduate education content (i.e., intellectual, occupational well-being) 84 and undergraduate medical education leadership (i.e., social, intellectual well-being). 33 A key finding was that well-being among learners is a multidimensional construct that includes 4 components: genuine sense of personal fulfillment and gratification in medical education, grounded understanding of requirements for medical education programs, enhanced peer cohesion and functionality, and promoting cognitive flexibility to strengthen knowledge for diverse perspectives.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Most (n = 12) focused on promoting and understanding intellectual well-being in medical education (Table 2). Five qualitative studies reported favourable outcomes; 3 studies concluded that formal audit is needed 34,79,77 and 2 studies uncovered shortcomings related to postgraduate education content (i.e., intellectual, occupational well-being) 84 and undergraduate medical education leadership (i.e., social, intellectual well-being). 33 A key finding was that well-being among learners is a multidimensional construct that includes 4 components: genuine sense of personal fulfillment and gratification in medical education, grounded understanding of requirements for medical education programs, enhanced peer cohesion and functionality, and promoting cognitive flexibility to strengthen knowledge for diverse perspectives.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Students with prior electives in cardiology were more likely to select cardiology as a top career choice compared to those without previous clinical time in cardiology. Elective exposure has been previously shown to increase student interest in that specialty, 18,19 However, to our knowledge this is the first Canadian study demonstrating that elective exposure is associated with increased likelihood of medical student selection of cardiology as a top career choice, which is pertinent for Canadian medical students as clerkship selectives are chosen during pre-clerkship training.…”
Section: Ijmsmentioning
confidence: 85%
“…To support early career navigation among medical students, undergraduate medical schools may look toward promoting student-led programs that enable students to gain clinical exposure to medical specialties outside of traditional undergraduate medical curricula, as these initiatives may increase student interest in these specialties. 18,19,27 The strengths of this study include the assessment of career-related factors of cardiology used in previous literature. 16,17 Additionally, the decision to assess the interest and understanding of students at the end of their pre-clerkship curriculum addresses the fact that medical students make career-impacting decisions early in their training without being fully informed.…”
Section: Ijmsmentioning
confidence: 99%
“…Exposure to a PM&R rotation in medical school has been shown to increase understanding of the specialty. 13 However, only 4 of 154 US medical schools (2%) currently have a required clerkship in PM&R and only 64% of US medical schools have an elective PM&R clerkship. 14 One reason for this lack of clerkships and electives may be due to the time constraints of existing faculty.…”
Section: Discussionmentioning
confidence: 99%